Електронний документ як складова електронного діловодства суб'єкта господарювання - Піддубна, Л. В. (НТУ "ХПІ", 2014)
Стаття присвячена дослідженню питань електронного діловодства. Метою статті є визначення сучасної ролі документа як інформаційного ресурсу і складової електронного діловодства суб'єкта господарювання. Простежено еволюцію тлумачення терміну "документ" у різних галузях знань та сферах суспільної діяльності. Основною відзнакою сучасного інформаційного суспільства стало утворення електронної документації, що трансформувало розуміння сутності документа, зміщуючи акценти з матеріальної її складової в інформаційну. Проаналізовано різні дефініції поняття "електронний документ", його ключові функції та середовище обігу, відмінності традиційного паперового документа від електронного. Запропоновано авторське визначення поняття "електронний документ".

Article is devoted to electronic records management. Aim is to determine modern role the document as an information resource and component of the electronic records management entity. The article suggests the evolution of the interpretation of the term "document" in a variety of fields and spheres of public activity. It is shown that the concept of "document" in different publications is formulated differently. The document is viewed as an important source of information and as a means of communication. Implementation of electronic documentation is the main difference the modern information society. This difference transforms the usual understanding of the essence of the document carries the essence of the document with the material component on the information content. The impact of computer technology on all spheres of public activity determines the value of the document as a tangible medium for recording information. The article contains various definitions of the terms "document" and "electronic document", an analysis of their core functions and environment circulation. Describes the properties and identified the differences between the traditional paper document and electronic document. The author offered his definition of "electronic document".
Electronic document as a component of an electronic records management of a business entity
Keywords: інформаційні ресурси; електронне діловодство; електронний документ; документ; електронний цифровий підпис; суб'єкт господарювання; document; electronic document; electronic digital signature; electronic records management; business entity